Underground Games: Surface Translation and the Grotesque - Fraser, Ryan (TTR)

(untitled) (Association canadienne de traductologie, 2016)
Referenced by theory for seemingly contradictory purposes, the practice of “surface translation” has an ambivalent status within Translation Studies. This is not surprising, as the principle of ambivalence informs both its composition and its conversation with its reader. Nevertheless, a positive step toward a more productive conception of surface translation was accomplished by Jean-Jacques Lecercle (1990), who defined it as a form in extremis of linguistic interference or mixing. Guided by this conception, I would argue here that the practice is in all respects identifiable with the Classical and Medieval ornamental style known by art history as the “grotesque.” This is the first study to identify surface translation with the grotesque. Five specific points of comparison are leveraged here: 1) Both surface translation and grotesque art are created through the proscribed mixing of incompatible materials; 2) Both are peripheral art forms involving play with margins; 3) Both aspire toward the “perverse,” “comic,” and/or “monstrous” in their mixes; 4) Both tend to be explained as the product of impulsive thinking; 5) The experience that these mixtures are designed to produce is “ambivalence.”